Adoption of information and communication technologies in teaching and learning at a university - Moyo, R. (South African Journal of Higher Education, 2019)
The study was a cross-sectional exploratory survey to determine lecturers’ and students’ use of the core e-learning site, e-Thuto, at the Central University of Technology, Free State (CUT). The goal was to determine the adoption of electronic learning via information and communication technologies (ICTs) towards the improvement of the quality of teaching and learning. Yet, research cites several resource and skills challenges hindering ICT adoption in teaching and learning in developing economies that remain unaddressed. Data were collected from 10 lecturers in the Department of Communication Sciences at the CUT and 90 undergraduate students from all the four CUT faculties in order to correlate lecturers’ and students’ perspectives. Therefore, a structured interview schedule was used. Data were analysed using the emic and etic approaches where the respondents’ categorisation of behaviour, correlated with conceptual categories from literature, was regarded as the reality in the study context. The findings indicate a limited adoption of e-Thuto in teaching and learning due to several impediments. The policy implications point towards a more systematic integration of ICTs into the curriculum.